Einfluss der Größe auf die Aufgabe der Tierproduktion: Empirische Analyse Milchvieh und Sauen haltender Betriebe in Deutschland; The Impact of Size on Exiting from Livestock Production - an Empirical Analysis of Dairy and Sow Farms in Germany - Insa Thiermann; Gunnar Breustedt; Carolin Rosenau (German Journal of Agricultural Economics (GJAE), 2019)
– We study the exit from livestock production of 35,000 German farms. By means of regression analysis we identify the factors affecting farmers' decisions either to quit farming altogether or to abandon certain livestock enterprises (sows and dairy cows). For our data, results from binomial probit estimations are either valid for quitting farming altogether or exiting from livestock production only. The determinants for these two decisions are different. Consequently, for analyzing the decision to exit from livestock production a multinomial probit model is preferred over a binomial model since a livestock farmer has three options to choose from: continuing livestock production, exiting from farming, or exiting from livestock production while keeping arable farming. For both dairy farms and sow farms we find that larger herd sizes make the abandonment of the respective livestock enterprises less likely. By contrast, the decision to quit farming altogether is not affected by herd size. We thus find no evidence in support of the much cited conjecture that the size of a farm's livestock enterprise increases the probability of its survival.
Keywords: 330